Oral Health Knowledge and Practices of Secondary School Students, Tanga, Tanzania - Carneiro, Lorna (Hindawi Publishing Corporation, 2011)
A good quality of life is possible if students maintain their oral health and become free of oral disease. A structured questionnaire assessed 785 students' level of oral health knowledge and practices. About 694 (88.4%) students had adequate level of knowledge on causes, prevention, and signs of dental caries, 760 (96.8%) on causes and prevention of periodontal diseases, 695 (88.5%) on cigarette smoking as cause of oral cancer, and 770 (98.1%) students on importance of dental checkups. Majority 717 (91.3%) had adequate practice of sugary food consumption; while 568 (72.4%) had acceptable frequency of tooth brushing, 19 (2.4%) brushed at an interval of twelve hours, and 313 (39.9%) visited for checkup. Majority of students had an adequate level of knowledge on oral health but low level of oral health practices. Both genders had similar level of knowledge with male predominance in oral health practices. Age had no influence on the level of oral health knowledge and practices of students.